2021
DOI: 10.1002/gcc.22982
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐192‐5p inhibits migration of triple negative breast cancer cells and directly regulates Rho GTPase activating protein 19

Abstract: Among the different breast cancer subtypes, triple‐negative breast cancer (TNBC) is associated with a poor prognosis, low survival rates, and high expression of histone deacetylases. Treatment with histone deacetylase inhibitor trichostatin A (TSA) leads to an increased expression of potential tumor‐suppressive miRNAs. Characterization of these miRNAs can help to find new molecular targets for treatment of TNBC. We identified differentially expressed miRNAs by microarray analyses after treatment with TSA in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A study on laryngeal cancer showed that hsa_circ_0023028 knockdown inhibits cell migration, proliferation, and invasion ( 22 ). Vajen et al reported that miRNA-192-5p inhibits the migration of triple-negative breast cancer cells and directly regulates Rho GTPase-activating protein 19 ( 23 ). However, hsa-miR-194-5p has not been the subject of any studies on OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A study on laryngeal cancer showed that hsa_circ_0023028 knockdown inhibits cell migration, proliferation, and invasion ( 22 ). Vajen et al reported that miRNA-192-5p inhibits the migration of triple-negative breast cancer cells and directly regulates Rho GTPase-activating protein 19 ( 23 ). However, hsa-miR-194-5p has not been the subject of any studies on OSCC.…”
Section: Discussionmentioning
confidence: 99%